USM ARCHAEOTOURISM PRODUCTS GET GOOD RESPONSE IN LONDON - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
LONDON, 9 November 2016 - Universiti Sains Malaysia (USM) is participating in the ongoing World Travel Mart (WTM) London 2016 programme where it showcased its highly acclaimed product on archaeotourism in Sungai Batu and Lenggong.